REFLECTIONS ON THE ACT OF JUDGING IN PAUL RICOEUR (Isagoge - Journal of Humanities and Social Sciences, 2022)
The decision of a case is the most awaited act by the parties and that, as a rule, puts an end to the legal demand. The purpose of this study is to present a brief reflection on Paul Ricoeur's article about the act of judging, and how other authors, both jurists and philosophers, also focus on what one could have as an ideal model for a fair decision. When approaching legal issues, the judgment - here considered as the final provision - is what is expected of the legal system, but, also, when philosophical questions are extracted from the judgment, its unfolding is important to analyze the pacification, or not. , of the social conflict and if, in that case in which the intervention of the State-Judge was necessary, there was the true correct realization of the applicable truth.
Keywords: Decision; Judgement; Paul Ricoeur; Conflict; Justice